Gas holdup in bubble column with suspended low density particles - Yao, Alexander Ka Gue
The fractional gas holdup in an air-water-solid suspension-bubble column was measured for the variable ranges listed below. The column used has an internal diameter of 9.4 cm while the solid particles have a density of 0.948 9/mL.